Instrumentos jurisdicionais para efetivação do direito à saúde: uma análise dos processos em tramitação na 1ª vara da Fazenda Pública da Comarca de Palmas - Reis Neto, Manuel de Faria (Universidade Federal do Tocantins, 2018)
The purpose of this dissertation is to analyze the efficacy of the judicial decisions pronounced in the comarca of the city Palmas/TO, they seek to garantee the access public health. The quantitative-qualitative method showed to the more adequate to the intending objetive, that is, the executive measure more efficacius for to garante the execution of the judicial decision that effective the constitutional right to health. The data collection was done through the analysis of judicial processes in course in the First Judicial Area of the Treasury and Public Registers of the City Palmas, whose decisions were granted of form anticipate or in-depth examination and which occurred between January 1, 2016 and November 20, 2017, always through the database of the State Court of Tocantins (E-proc). Were excluded from the analysis the cases in which the pleadings had been reject, collective demands, as well as the processes that be in course or process that was in curso in secrecy of justice, being limited to the facts open to the public consultation. In addition to the result obtained with the application of the data collection instrument, a varied bibliographic material which occurred through consultations on books, scientific articles, legislation, judgments of High Courts and websites. The results indicate that, for each provision sought, either by access to a medicinal product or by surgical procedure, hospitalizations or other forms of intervention , there is a more appropriate executive measure, being coercive or subrogation. Always striving for proportionality between constitutional law, but above all, on the effectiveness of a decent health right.